Tobacco and alcohol: complements or substitutes? - Harald Tauchmann; Silja Lenz; Till Requate; Christoph M. Schmidt (Empirical Economics, 2013)
The question of whether alcohol and tobacco are consumed as complements or substitutes is crucial for determining the side-effects of anti-smoking policies. Numerous papers have empirically addressed this issue by estimating demand systems for alcohol and tobacco, and subsequently calculating cross-price effects. However, this traditional approach is often seriously hampered by insufficient price variation observed in survey data. We, therefore, suggest an alternative instrumental variables approach that statistically mimics an experimental study and does not rely on prices as explanatory variables. This approach is applied by means of German survey data. Our estimation results suggest that a reduction in tobacco consumption results in a moderate reduction in alcohol consumption. It is demonstrated that this implies that alcohol and tobacco are complements. Hence, we conclude that successful anti-smoking policies will not result in the unintended side-effect of an increased (ab)use of alcohol.
Keywords: C31; D12; I12; 330; Complements or substitutes; Interdependence in consumption; Tobacco and alcohol; Insufficient price-variation; Instrumental variables approach